2015
DOI: 10.1140/epjc/s10052-015-3775-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of resonance regeneration and decay on the net proton fluctuations in a hadron resonance gas

Abstract: We investigate net-proton fluctuations as important observables measured in heavy-ion collisions within the hadron resonance gas (HRG) model. Special emphasis is given to effects which are a priori not inherent in a thermally and chemically equilibrated HRG approach. In particular, we point out the importance of taking into account the successive regeneration and decay of resonances after the chemical freeze-out, which lead to a randomization of the isospin of nucleons and thus to additional fluctuations in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 71 publications
3
80
1
Order By: Relevance
“…Resonance decays contribute significantly to the final state particle multiplicities and, consequently, to event-byevent multiplicity distributions. Their impact on net-proton number fluctuations, ignoring the possible presence of a critical point, was previously studied in [30,31]. It was found that the decay processes do not significantly modify the primordial (without resonance decays) ratios of net-proton number cumulants if the probabilistic decay contributions are properly taken into account [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resonance decays contribute significantly to the final state particle multiplicities and, consequently, to event-byevent multiplicity distributions. Their impact on net-proton number fluctuations, ignoring the possible presence of a critical point, was previously studied in [30,31]. It was found that the decay processes do not significantly modify the primordial (without resonance decays) ratios of net-proton number cumulants if the probabilistic decay contributions are properly taken into account [31].…”
Section: Introductionmentioning
confidence: 99%
“…Their impact on net-proton number fluctuations, ignoring the possible presence of a critical point, was previously studied in [30,31]. It was found that the decay processes do not significantly modify the primordial (without resonance decays) ratios of net-proton number cumulants if the probabilistic decay contributions are properly taken into account [31]. This is because a thermal distribution of particles is being folded with a binomial decay distribution yielding again a nearly thermal distribution.…”
Section: Introductionmentioning
confidence: 99%
“…However, taking into account the effects of resonance feed-down and isospin randomization [36,37], one can show that the net-proton and net-baryon number fluctuations are numerically very similar, at least in the case of low-order fluctuations [38].…”
Section: Fluctuations Of Conserved Chargesmentioning
confidence: 99%
“…To calculate the resonance decay contributions to kurtosis in the CE include four nested loops over all particles and resonances, which is again fairly computing time consuming. In recent studies [21,22], the resonance decay contributions have been divided into an average and a probabilistic part. For example, in Eq.…”
Section: Effect Of Resonance Decaysmentioning
confidence: 99%
“…Most calculations [17][18][19][20][21][22][23] on higher moments of multiplicity fluctuations in the HRG model employed only the GCE treatment. To approximately achieve conditions of the GCE, one is required to study fluctuations in a restricted phase space [24,25].…”
Section: Introductionmentioning
confidence: 99%